2018
DOI: 10.1128/mbio.01683-18
|View full text |Cite|
|
Sign up to set email alerts
|

Treatment of Human Glioblastoma with a Live Attenuated Zika Virus Vaccine Candidate

Abstract: Glioblastoma (GBM), the deadliest type of brain tumor, is currently incurable because of its high recurrence rate after traditional treatments, including surgery to remove the main part of the tumor and radiation and chemotherapy to target residual tumor cells. These treatments fail mainly due to the presence of a cell subpopulation called glioma stem cells (GSCs), which are resistant to radiation and chemotherapy and capable of self-renewal and tumorigenicity. Because Zika virus (ZIKV) has an oncolytic tropis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
102
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(109 citation statements)
references
References 38 publications
2
102
1
4
Order By: Relevance
“…We and others have previously shown that certain lines of brain tumors with stem cell-like genetic programs, such as glioblastomas, are highly susceptible to ZIKV infection [29,4547]. These cells display a striking phenotypic change upon infection.…”
Section: Resultsmentioning
confidence: 99%
“…We and others have previously shown that certain lines of brain tumors with stem cell-like genetic programs, such as glioblastomas, are highly susceptible to ZIKV infection [29,4547]. These cells display a striking phenotypic change upon infection.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, glycine mutations affecting exon 49 of the COL1A2 gene was associated with an increased risk of intracranial bleeding 34 . Both collagen and LOX genes are stimulated in glioblastoma cells, and the suppression of this pathway by ZIKV infection could explain the decreasing of angiogenesis and anticancer effects that several authors are exploring to treat glioblastoma [35][36][37] with ZIKV-like particles.…”
Section: Discussionmentioning
confidence: 99%
“…In an orthotopic glioma model, the live attenuated ZIKV reduced intracerebral tumor growth and prolonged animal survival. In these studies, a selective killing on GSCs within the tumor was observed [26]. Recent findings demonstrate that the entry of ZIKV into GSCs is supported by Integrin α v β 5 because viral entry can be specifically blocked by an α v β 5 -specific antibody or by the cyclic peptide Cilengitide (cyclo-RGDfV-) [27], a peptide that is highly specific for binding to α v integrin [28][29][30].…”
mentioning
confidence: 96%
“…In mice, ZIKV infection prolonged survival by slowing down tumor growth and showed only a weak side effect on normal neural cells [25]. Following these observations, the safety and efficiency of a live attenuated ZIKV candidate was investigated [26]. In an orthotopic glioma model, the live attenuated ZIKV reduced intracerebral tumor growth and prolonged animal survival.…”
mentioning
confidence: 99%